FEATURES OF MEMORY DEVELOPMENT IN CHILDREN IN PRESCHOOL EDUCATION WHEN LEARNING A FOREIGN LANGUAGE (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article provides information about the features of memory development in children in preschool education when learning a foreign language. Also, ideas about the types of memory abilities of a child are expressed.
Keywords: Visual memory, preschool childhood, verbal logical memory, ability column, special movement, speech and thinking, stanza.